2016
DOI: 10.1123/ijsnem.2015-0218
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Status and Daytime Pattern of Protein Intake on Match, Post-Match, Rest and Training Days in Senior Professional and Youth Elite Soccer Players

Abstract: The nutritional status of elite soccer players across match, post-match, training and rest days has not been defined. Recent evidence suggests the pattern of dietary protein intake impacts the daytime turnover of muscle proteins and, as such, influences muscle recovery. We assessed the nutritional status and daytime pattern of protein intake in senior professional and elite youth soccer players and compared findings against published recommendations. Fourteen senior professional (SP) and fifteen youth elite (Y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
46
2
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(56 citation statements)
references
References 19 publications
(37 reference statements)
6
46
2
2
Order By: Relevance
“…Interestingly, absolute and relative daily protein intakes were higher (205 ± 30 g) than that reported two decades ago in British professional players (108 ± 26 g), whereas both CHO and fat intake were relatively similar (Maughan, 1997). Our observed daily protein intakes also agree well with those reported recently (150-200 g) in adult professional players from the Dutch league (Bettonviel et al, 2016). Such differences between eras are potentially driven by the increased scientific research and resulting athlete (and coach) awareness of the role of protein in facilitating training adaptations and recovery from both aerobic and strength training (Moore et al, 2014;McNaughton et al, 2016).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Interestingly, absolute and relative daily protein intakes were higher (205 ± 30 g) than that reported two decades ago in British professional players (108 ± 26 g), whereas both CHO and fat intake were relatively similar (Maughan, 1997). Our observed daily protein intakes also agree well with those reported recently (150-200 g) in adult professional players from the Dutch league (Bettonviel et al, 2016). Such differences between eras are potentially driven by the increased scientific research and resulting athlete (and coach) awareness of the role of protein in facilitating training adaptations and recovery from both aerobic and strength training (Moore et al, 2014;McNaughton et al, 2016).…”
Section: Discussionsupporting
confidence: 81%
“…For example, both daily absolute energy and relative CHO was greater on match days (3789 ± 532 kcal and 6.4 ± 2.2 g·kg -1 , respectively) compared with training days (2948 ± 347 kcal and 4.2 ± 1.4 g·kg -1 , respectively). Such differences in daily EI also agrees with recent observations from adult professional players of the Dutch league (Bettonviel et al, 2016) where subtle differences were observed between match days, training days and rest days (3343 ± 909, 3216 ± 834 and 2662 ± 680 kcal, respectively). It is also noteworthy that we observed greater energy intake on day 7 (before another match undertaken on day 8) versus day 4 (before match day 2).…”
Section: Discussionsupporting
confidence: 80%
“…sprovedena kod zdravstvenih radnika u Meksiku, Južnoj Africi i Kini i profesionalnih sportista, fudbalera u Holandiji, tenisera u Francuskoj i odbojkaša i košarkaša u Crnoj Gori. [5][6][7][8][9][10] U pomenutom istraživanju sprovedenom u Baru uključena je mlada, odrasla populacija oba pola. Utvrđene su značajne razlike između sportista i osoba koje nisu sportisti u pogledu uhranjenosti, konzumiranja doručka i pijenja vode.…”
Section: Stručni Rad / Professional Article Uvodunclassified
“…So, adequate muscle glycogen stores provide a significant protein-sparing effect during soccer matches and hard workouts. Some studies highlight the inadequacy of carbohydrate intake in professional soccer players (2,8) what can elicit a larger incidence on protein metabolism to support energy demands. There are three fatty acids which are essential for the body's survival.…”
mentioning
confidence: 99%